Brain Death and Special Circumstances - Kerem Erkalp (Galenos Yayinevi, 2023)
The basis for the diagnosis of brain death (BD) is defined for the detection of a clinical condition with minimal criteria. The patient's current condition or the presence of organ support treatments for efforts to keep the patient alive in this process may cause difficulties to brain death diagnose for clinicians. In this article, information on processes in special conditions such as extracorporeal membrane oxygenation support, pregnancy, and hypernatremia during the diagnosis of BD is shared.